2020
DOI: 10.1088/1741-2552/ab7a50
|View full text |Cite
|
Sign up to set email alerts
|

Improved functional connectivity network estimation for brain networks using multivariate partial coherence

Abstract: Objective. Graphical networks and network metrics are widely used to understand and characterise brain networks and brain function. These methods can be applied to a range of electrophysiological data including electroencephalography, local field potential and single unit recordings. Functional networks are often constructed using pair-wise correlation between variables. The objective of this study is to demonstrate that functional networks can be more accurately estimated using partial correlation than with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…At the same time, the increase in the average path length between nodes reduces the efficiency of information transmission in the global scope. In previous studies, by comparing the functional network structure of patients with temporal lobe epilepsy and healthy people, it was found that the increase in CC and CPL in patients with epilepsy led to the development of a functional network with a more regular structure ( 24 ). This regular network structure was more vulnerable to the influence of abnormal discharge compared with the small-world network ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the increase in the average path length between nodes reduces the efficiency of information transmission in the global scope. In previous studies, by comparing the functional network structure of patients with temporal lobe epilepsy and healthy people, it was found that the increase in CC and CPL in patients with epilepsy led to the development of a functional network with a more regular structure ( 24 ). This regular network structure was more vulnerable to the influence of abnormal discharge compared with the small-world network ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it is therefore crucial to isolate this contribution and eventually remove it from the estimate [50,51]. While the large part of the FC methods have tended to neglect third-party influences, there are now several methods in literature, based on partial coherence [33,52] or partial directed coherence [40], which have been designed to circumvent and alleviate those spurious effects.…”
Section: Directedmentioning
confidence: 99%